Superior Mesenteric Artery–Pancreaticoduodenal Arcade Bypass Grafting for Repair of Inferior Pancreaticoduodenal Artery Aneurysm with Celiac Axis Occlusion - Murata, Akira (Ann Vasc Dis, 2018)
We report a case of an aneurysm of the inferior pancreaticoduodenal artery (IPDA), with chronic occlusion of the celiac axis. Both surgical aneurysmectomy and endovascular coil embolization were anticipated to sacrifice IPDA, which could lead to severe acute ischemia in the celiac region. The treatment involved surgical ligation of the aneurysm after bypass grafting from the superior mesenteric artery to the anterior IPDA. A postoperative computed tomography revealed no enhancement of the aneurysm and sufficient collateral blood supply by the patent bypass graft.